HEAVY LIFTING FOR OF E-HOUSE MUDULE 245 T, USING CRAWLER CRANE 1250 T - Mutadi, Mutadi (Mestro: Jurnal Teknik Mesin dan Elektro, 2023)
Abstract. Heavy lifting on an E-House Module 245 T is using Crawler Crane 1250 T with single lifting while moving on the soft soil ground is most riski and prone to the setllement. The heavy module that are lifted in unstable ground bearing areas will move due to the settlement from soil which can cause damage to module. A site activity of the lifting plan of the module used Crawler Crane 1250 T was conducted to investigate the effect of radius operation and COG Centre of Gravity to be considered for the lifting plan. In this result the rigging sling get safety factor as the lowest it is 1.06, the crawler crane get safety factor is 1.22 and the ground bearing safety factor is 1.53. The load from E-House Module get from the weigingb report is 245 T with the COG XCG 7860 mm , YCG 437 mm and ZCG 5840mm, the module dimension is 18200 mm x and 9000 mm y and 16400 mm z.